Catalyzing Sustainable Futures: Innovative Approaches in Capacity Building for the Community Engineering Response Team - Musa, Tagwa; Elsayed, Fatima; Alawad, Ali; Babiker, Romysaa; Mahmoud, Bakry; Fadul, Nada; Jordan, Ramiro; Elbashir, Nimir (World Engineering Education Forum - Global Engineering Deans Council (Online), 2024)
This paper presents a comprehensive capacity-building program designed for engineering students in Sudan, with a focus on fostering a Community Engineering Response Team (CERT). In response to a pressing scarcity of essential services in many communities, this initiative aims to equip engineering students with the knowledge and skills necessary to address local challenges and promote community self-reliance. The program is rooted in the ECHO model of All-Teach All-Learn, peace engineering principles, and the Sustainable Development Goals framework.Utilizing a virtual academic-community learning environment, Sudanese college students, young professionals, women and men of all ages, and youth were engaged in 18 biweekly sessions on solid waste management, along with an additional 5 sessions focused on design-centered entrepreneurship. These sessions, facilitated by national and international subject matter experts, employed a participatory approach and attracted approximately 700 participants from 11 engineering disciplines across 8 Sudanese universities in 6 different states.Post-program evaluations indicate significant knowledge enhancement, with 94.4% of participants reporting a heightened understanding of solid waste management benefits. A majority (78.7%) expressed a willingness to recommend the program, citing a balanced mix of lectures and interactivity (86.9%). Moreover, 74.7% intended to apply the acquired knowledge in their professional pursuits.Following the capacity-building phase, 40 participants progressed to the implementation stage, selecting projects aligned with community needs. These projects encompassed a community awareness program in rural areas, biogas, and compost production from organic waste, interlock production from plastic waste and sand, and Geographic Information System (GIS) mapping for solid waste. These engineers, who are actively engaged in the program, form the core of the Community Engineering Response Team (CERT), which is dedicated to addressing community challenges through sustainable engineering solutions.